The Effect of Competence, Motivation and Job Satisfaction on Personnel Performance in Kupus II Ditkuad - Fitri Anggraeny; Ferikawita Magdalena Sembiring (Fakultas Ekonomi dan Bisnis, Universitas Jenderal Achmad Yani, 2025)
This type of research is a primary research with a quantitative approach. There is also the collection of data with questionnaires and documentation studies. The data used in this study is in the form of an annual report of the Kusatker Kupus II Ditkuad. The number of samples in this study was 130 people consisting of the TNI and civil servants. The sample determination technique used is random sampling with several criteria that the researcher determines. The analysis method used is multiple linear regression analysis which has previously gone through classical assumption testing and significance testing using SPSS 25 software. The results of this study show that (1) Competency variables have a positive and significant effect on personnel performance. (2) Motivation variables have a positive and significant effect on personnel performance. (3) Job satisfaction variables have a positive and significant effect on personnel performance. (4) Variables of competence, motivation and job satisfaction simultaneously affect personnel performance.